Focal Segmental Glomerulosclerosis in Waldenström’s Macroglobulinemia - Akshee Batra; Shatha Herz Allah; Bijin Thajudeen (Case Reports in Nephrology)
Renal involvement in Waldenström’s macroglobulinemia is a rare manifestation. Although most renal involvement is due to monoclonal immune deposits, pathology can also be unrelated to it. Here, we describe a 68-year-old female with a history of Waldenström’s macroglobulinemia who presented with generalized edema and nephrotic range proteinuria. A renal biopsy showed findings consistent with focal segmental glomerulosclerosis. Treatment with oral prednisone leads to the resolution of proteinuria. This case highlights the importance of identifying pathology that might not be directly related to monoclonal gammopathy, which could have implications on the management.